Development of Vegetative Propagation Technology of Teak Plant in Small Holder Forest - Adinugraha, Hamdan Adma; Mahfudz, Mahfudz (Balai Penelitian Kehutanan Manado, 2014)
Teak (Tectona grandis) is one of popular and important carpentry wood in Indonesia. However teak production for carpentry material cannot balance the increasing need for domestic and export market. The increased production from small holder forest can be alternative way to supply national wood need. Therefore science and technology play role to support forest productivity eg superior seedling from vegetative propagation. The preparing of superior seed took several steps i.e. selection from mother tree, genetic material extraction, grafting activity using budding technique, hedge orchard establishment, and mass production used cutting rotted or tissue culture. From clonal test we can derive superior seed which adaptive with development location and has better productivity.